1994
DOI: 10.1111/j.2042-7158.1994.tb03719.x
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid Action of Ketoconazole: In-vitro Studies and Rat In-vivo Studies

Abstract: Inspection of the chemical structure of ketoconazole indicates that it may have antithyroid activity. The antithyroid action of this drug was demonstrated in-vitro and in-vivo. In-vitro, it was found to form a complex with iodine (formation constant Kc 141 L mol-1), and to inhibit lactoperoxidase (IC50 2 x 10(-4) M). Its effects in-vivo in the rat were assessed by assay of circulating-thyroxine, and from the histological appearance of the thyroid gland. Thyroid gland weight was increased in rats treated with k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In preclinical studies, imidazoles, such as ketoconazole, have had antithyroid effects because of interference with iodine and thyroid peroxidase. 56 Nevertheless, administration of 200 to 600 mg/d of ketoconazole for 1 month did not affect thyroid function in euthyroid, hyperthyroid, or hypothyroid patients. 57,58 However, high-dose ketoconazole (1200 mg/d) may cause hypothyroidism.…”
Section: Antifungal Agentsmentioning
confidence: 88%
“…In preclinical studies, imidazoles, such as ketoconazole, have had antithyroid effects because of interference with iodine and thyroid peroxidase. 56 Nevertheless, administration of 200 to 600 mg/d of ketoconazole for 1 month did not affect thyroid function in euthyroid, hyperthyroid, or hypothyroid patients. 57,58 However, high-dose ketoconazole (1200 mg/d) may cause hypothyroidism.…”
Section: Antifungal Agentsmentioning
confidence: 88%
“…Many other compounds have been found to affect thyroid hormone synthesis without interfering directly with thyroperoxidase (Gaitan 1988;Capen 1992;Gittoes & Franklyn 1995). In previous studies (Raby et al 1990;Comby et al 1994;Lagorce et al 1995) we showed that many drugs which inhibit thyroperoxidase form charge-transfer complexes with iodine. If these molecules, which are also strong electron-donors, accumulate in the thyroid gland they would tend to sequester iodine, thereby mimicking iodine de®ciency.…”
mentioning
confidence: 89%
“…Reduction of immunosuppression may prove helpful in disseminated disease. In preclinical studies, imidazoles, such as ketoconazole, have had antithyroid effects because of interference with iodine and thyroid peroxidase [9]. Nevertheless, administration of 200 to 600 mg/d of ketoconazole for 1 month did not affect thyroid function in euthyroid, hyperthyroid, or hypothyroid patients [3].…”
Section: Discussionmentioning
confidence: 99%